Implementation of the Analytical Hierarchy Process (AHP) Method to Support Selection of HCI Life Insurance Products - Irsan Jaelani; Minarto; Kaniawulan, Ismi; Sri Andar Muni, Lise; Mahendra, Andi (RISTEC : Research in Information Systems and Technology, 2024)
Decision Support Systems (DSS) or Decision Support Systems (DSS) is an information system that is flexible, interactive, can be adapted and developed to provide information, modeling and data manipulation so that it can produce various alternative decisions and answers to assist management in dealing with various problems that arise. semi-structured and unstructured situations, where no one knows for sure how decisions should be made. One method that can be used is the Analytical Hierarchy Process (AHP) method. This method was chosen because it can describe complex multi-factor or multi-criteria problems into a hierarchy that is implemented in the selection of insurance products using the AHP method. With this method it is expected to be able to choose the right product because it is based on predetermined criteria and weight values so that it will get maximum results.